Communication Mechanisms and Implications of the COVID-19 Risk Event in Chinese Online Communities - Pengpeng, Li; Fangqi, Zhong; Qianru, Zhuo (Frontiers in Public Health, 2022)
Based on the context of communication and use of online communities in China, this study explored the characteristics and defects of risk communication of the government and official media in the event of COVID-19, as well as the factors that affected people's perception of the risk and protective behavior. The following results were found: (1) The government and official (mainstream) media accounts suffered from information lag in the early stage of COVID-19, while self-media accounts played the role of risk sensors, which caused people to have less trust in the government and the authorities and turn to the truth on self-media accounts. However, the low accessibility of self-media accounts and the imperfect check mechanism provided a hotbed for rumors, which further led to more fear and worry about risks. (2) During the middle and later periods of COVID-19, the government and the official media began to pay attention to the influence of self-media on peoples' emotions and behavior, and gradually improved the supervision of online information and the operation of official media accounts. This is intended to achieve information consistently and link mechanisms between official media and self-media to prevent and correct mistakes, as well as to achieve effective risk communication of information transparency, opinion exchange, and public sentiment stabilization.